2019
DOI: 10.1371/journal.pone.0217744
|View full text |Cite
|
Sign up to set email alerts
|

Human coronavirus alone or in co-infection with rhinovirus C is a risk factor for severe respiratory disease and admission to the pediatric intensive care unit: A one-year study in Southeast Brazil

Abstract: Objective We aimed to assess the profile of respiratory viruses in young children hospitalized for acute lower respiratory tract infection (ALRI) and its association with disease severity, defined as need for pediatric intensive care unit (PICU) admission. Design Prospective observational cohort study. Setting A tertiary-care university hospital in Brazil. Patients Children younger than three years attending the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
0
22
1
4
Order By: Relevance
“…The proportion of patients with increased white blood cells and neutrophils in the older age groups was significantly higher than that in the younger age group. These findings suggest that older patients may be more likely to have a secondary infection with other bacteria, which may lead to poor prognosis [28]. Kim et al reported that viral-bacterial coinfection was an independent predictor of mortality from viral pneumonia [29].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with increased white blood cells and neutrophils in the older age groups was significantly higher than that in the younger age group. These findings suggest that older patients may be more likely to have a secondary infection with other bacteria, which may lead to poor prognosis [28]. Kim et al reported that viral-bacterial coinfection was an independent predictor of mortality from viral pneumonia [29].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of determining the local epidemiology, and suggests that genomic sequencing of isolates may be a necessary next step to investigate genetic changes over time. Interestingly, there is increasing reports of both co-infections with multiple respiratory viruses and viral and bacterial pathogens, and data suggesting this may be associated with more severe disease [25][26][27][28]. In our cohort bacterial co-infections were only identified in 7.9 % of individuals, and viral co-infections in 3.1 %; both of which are lower than what has been reported by other groups [28,29], and we did not have sufficient numbers to investigate any correlations with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with other respiratory viruses, before COVID‐19, has been described and should not be surprising. One study found that there was codetection of 2 or more viruses in 78% of patients requiring hospitalization for respiratory illness 5 . Of those, coinfection with human coronavirus (non‐SARS‐CoV‐2) together had an increased association with pediatric ICU admission.…”
Section: Discussionmentioning
confidence: 99%